Emotion dysregulation as a mechanism linking posttraumatic stress disorder to subsequent suicidal thoughts and behaviors following inpatient psychiatric discharge. (May 2023) - Raudales, Alexa M.; Carosa, Catarina L.; Weiss, Nicole H.; Schatten, Heather T.; Armey, Michael F.
Abstract: Posttraumatic stress disorder (PTSD) is a well-known risk factor for suicidal thoughts and behaviors (STBs). However, there is a scarcity of longitudinal studies exploring underlying pathways. This study sought to examine the mechanistic role of emotion dysregulation in the relations between PTSD and STBs following discharge from psychiatric inpatient treatment, a particularly high-risk period for suicide. Participants were 362 trauma-exposed psychiatric inpatients (45% female, 77% white, M age  = 40.37). PTSD was assessed via a clinical interview (Columbia Suicide Severity Rating Scale) during hospitalization, emotion dysregulation was assessed via self-report 3-weeks post-discharge, and STBs were assessed via a clinical interview 6-months post-discharge. St'1ructural equation modeling showed that emotion dysregulation significantly mediated the relation between PTSD and suicidal thoughts ( β  = 0.10, SE  = 0.04, p  = .01, 95% CI [0.04, 0.39]) but not suicide attempts ( β  = 0.04, SE  = 0.04, p  = .29, 95% CI [-0.03, 0.12]) post-discharge. Findings highlight a potential clinical utility of targeting emotion dysregulation among individuals with PTSD to prevent suicidal thoughts following discharge from psychiatric inpatient treatment. Highlights: PTSD increases risk for suicide, though mechanisms are poorly understood. We examined suicide risk in the six months after inpatient psychiatric discharge. Emotion dysregulation explained the link between PTSD and suicidal thoughts.